Local perceptions of ecosystem services and protection of culturally protected forests in southeast China - Hong Gao (Taylor & Francis Group, 2018)
Introduction: Culturally protected forests (CPFs), preserved and managed by local people on the basis of traditional practices and beliefs, have social and ecological functions. Local residents’ perceptions were investigated in three types of CPFs (community forests, ancestral temple forests, and cemetery forests) in five villages in southeast China. In semi-structured interviews (232 questionnaires), residents were asked about their perceptions concerning ecosystem services and protection of CPFs. Outcomes: The survey results showed that resource utilization was not high in CPFs than in forests without culturally protected. Important ecosystem services provided by CPFs included air quality improvement, water retention, recreation, and aesthetic value. Respondents were satisfied with different cultural services provided by CPFs, including aesthetic value of community forests, ecotourism of ancestral temple forests, and cultural heritage of cemetery forests. Informal rules and traditional customs were used as the main measures to govern forests in daily life; however, the most effective measures, in order of importance, were setting fines or punishment by laws, using informal rules and village regulations, or protection by government agencies. Only half of the respondents were willing to pay for maintaining ecosystem services of CPFs, but 77.8% respondents were willing to spend time on protection. From apolicy perspective, educational programs were as important as traditions, and they are crucial to explain the ecological importance of CPFs. Conclusion: The conservation of biodiversity and ecosystem services of CPFs will benefit if government agencies consider incorporating CPFs into policy and legislative frameworks, maintain CPFs as collectively owned forests, and introduce ecological compensation mechanisms.